The generalization of shared reality: When communication about one target shapes evaluations of other targets. (29th May 2015) - Bebermeier, Sarah; Echterhoff, Gerald; Bohner, Gerd; Hellmann, Jens H.
Abstract Communicators often tune their message about a target to the audience's attitude toward that target. This tuning can shape a communicator's own evaluation of the target, which reflects the creation of a shared reality with the audience. So far, evidence for shared‐reality creation has been confined to one specific target. In two experiments, we examined whether and when a shared reality would generalize to other targets. In Experiment 1, shared‐reality creation about an ambiguous sexist target generalized to the evaluation of a new ambiguous sexist target for which no audience attitude was provided. However, this happened only when there was high (vs. low) commonality with the audience regarding previous judgments. In Experiment 2, we investigated conditions for the temporal persistence of generalization. One week after message tuning to a high‐commonality audience, a shared reality generalized to a new ambiguous sexist target when participants recalled the shared‐reality creation about the initial target, but it did not generalize in conditions without such recall. Also, no generalization occurred for non‐ambiguous or non‐sexist targets. Results suggest that shared reality generalization depends on perceived commonality with the audience, recollection of shared reality at time of judgment, and similarity between new and initial targets.